Factors Affecting Customer Loyalty in Products - Romdonny, Jefry; rosmadi, maskarto lucky nara (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to determine the factors that can influence consumers have loyalty to a product produced by a company. The research method used is a qualitative method with a descriptive analytical approach. From the results of research conducted, it is known that customer loyalty is needed by producers, especially to market their products as well as the commitment of management to provide satisfactory service and quality products needed by consumers. The role of the government is often needed especially to overcome the high price of production raw materials because it is still imported from abroad.